S55 Pulmonary fibrosis with and without co-existing connective tissue disease: does it affect survival?. (16th November 2010) - Navaratnam, V; Ali, N; Smith, CJP; Fogarty, A; Hubbard, R B
Abstract : Introduction: The impact of co-existing connective tissue disease on the survival of patients with pulmonary fibrosis remains unclear, since studies into the subject have so far yielded varying results. This study compares the survival of individuals with idiopathic pulmonary fibrosis (IPF) to those with connective tissue disease associated pulmonary fibrosis (CTD-PF) using data from The Health Improvement Network (THIN), a large general practice database in the UK. Methods: Incident cases of individuals with IPF and CTD-PF between the years 2000 and 2008 were identified. Survival analysis was performed on this dataset using Kaplan–Meier methods and Cox regression was used to compare mortality rates between patients with IPF and CTD-PF, adjusting for age and gender. Results: During the study period, there were 2208 incident cases of IPF, who were predominantly male (64%) and had a mean age at time of diagnosis of 73.9 years (95% CI 73.5 to 74.4 years). In comparison there were 318 incident cases of CTD-PF, of which the majority were female (56%) and the mean age at time of diagnosis was 67.8 years (95% CI 66.6 to 68.9). The commonest connective tissue disease associated with pulmonary fibrosis was rheumatoid arthritis (211 cases), followed by systemic sclerosis (39 cases). The mean follow-up period after diagnosis for our cohort was 2.4 person years and during this period 1117 (51%) patients with IPF and 116 (36%) patients with CTD-PF had died. The mortality rates for patients with IPF and CTD-PF were 221 (95% CI 208 to 234) and 121 (95% CI 101 to 146) deaths per 1000 person years respectively. The median survival for patients with CTD-PF was significantly higher at 6.5 years compared to 3.2 years in patients with IPF (p=0.0033) (See Abstract S55 Figure 1 ). After adjusting for age and gender, patients with IPF had a worse prognosis compared to those with CTD-PF (HR 1.32, 95% CI 1.08 to 1.60). Conclusion: Individuals who have CTD-PF have a better prognosis after diagnosis when compared to those with IPF. This may relate to the differing natural histories of the diseases and needs further investigation.